Comparative evaluation of sensititre YeastOne and VITEK2 antifungal susceptibility tests with CLSI broth microdilution method of clinical Cryptococcus isolates in Taiwan - Tzu-Ping Weng; Shin-Wei Wang; Shih-Ting Lo; Shu-Li Su; Ming-I Hsieh; Pei-Jane Tsai; Pei-Fang Tsai; Chi-Jung Wu; Nan-Yao Lee; Wen-Chien Ko; Po-Lin Chen (Microbiology Spectrum)
ABSTRACT Commercial antifungal susceptibility tests were available for clinical yeast isolates. However, the updated Sensititre YeastOne (SYO) version YO10C excluded Cryptococcus species for susceptibility testing. Uncorrelation of antifungal susceptibility patterns by SYO and therapeutic outcomes had been recently reported. We compared the performance of current commercial susceptibility tests with the standard CLSI broth microdilution (BMD) method for clinical Cryptococcus isolates. Forty-seven clinical Cryptococcus isolates were included from 1 January 2012 to 30 June 2023, among which 44 isolates were Cryptococcus neoformans while 3 were Cryptococcus gattii. The performance of SYO version YO10C and VITEK2 YS09 was compared with the CLSI BMD method and correlated with MLST analysis and ERG11 mutation detection. Non-wild-type (non-WT) strains to amphotericin B (AMB) were observed in 11 isolates with the CLSI BMD method and 8 with SYO among 44 C. neoformans isolates, but only 1 isolate was classified as non-WT by both methods. Additionally, all C. neoformans isolates were susceptible to AMB with their MIC ≤1 µg/mL according to the clinical breakpoint defined by EUCAST. Non-WT to FLC were observed in 5 C. neoformans isolates with SYO, but they were classified as WT by CLSI BMD and VITEK2. The essential agreements between SYO and CLSI BMD were >90% to most antifungal agents except ITC in C. neoformans isolates (64%) and AMB in C. gattii group (67%). Between SYO and CLSI BMD, the major error (ME) rates were 11% (n = 5) to FLC, 5% (n = 2) to ITC, and 2% (n = 1) to 5FC in C. neoformans isolates, and the very major error to 5FC was found in one C. gattii isolate. ERG11 mutation with identical I199V was detected in 89% (n = 39) C. neoformans isolates, and 97% (n = 38) of them belonged to sequence type (ST) 5. The ERG11 mutation or cryptococcal ST was not associated with a decrease of antifungal susceptibilities. ME of FLC by SYO version YO10C compared to the CLSI BMD method reached up to 11% of C. neoformans isolates. The results of FLC MIC by SYO should be interpreted cautiously and correlated with therapeutic response, and further verification with the CLSI BMD method or VITEK2 is required.IMPORTANCEThe study pointed out the major errors of fluconazole susceptibility results in clinical Cryptococcus neoformans isolates between the commercial Sensititre YeastOne Susceptibility Plate version YO10C and the standard CLSI broth microdilution method. The results should be interpreted carefully with clinical correlation, and a different method of antifungal susceptibility testing should be considered if a discrepancy of susceptibility results is suspected.